Forest Fire: A Review - Savita; Sharma, S. K.; Singh, Hukum; Singh, Ombir (Indian Forester, 2017)
Fire is a vital and natural part of the functioning of numerous forest ecosystems. Forest fires are considered to be a potential hazard with physical, biological, ecological and environmental consequences. In India, forests fires are the most significant, and a steadily increasing factor in the degradation process, although the extent of total damage is widely disputed. In this review ecological, economic and social impact of the forest fire and possible future strategy to combat forest fire through skill development of affected societal groups has been described.